Effect of the Austenitizing Parameters on the Microstructure and Mechanical Properties of 75cr1 Tool Steel - Castro-Cerda, F (Elsevier Ltd, 2020)
The austenitizing heat treatment of the 75Cr1 tool steel was optimized in order to obtain high yield strength and toughness. Samples were austenitized at different temperatures and soaking times, and subsequently quenched and tempered. The phase transformation characteristics during heating and quenching were studied by dilatometry. Optical microscopy, electron backscatter diffraction, x-ray diffraction and transmission electron microscopy were used to characterize the microstructure, while tensile tests and toughness tests were employed to determine the mechanical properties after various heat treatments. It was found that both yield strength and toughness decrease with increasing austenitizing temperature. Thermodynamic and kinetic calculations with Thermocalc and Dictra software were used to study the movement of the austenite-carbide interface and the compositional gradients in the microstructure at different austenitizing conditions. Based on the calculations it was found that the rate of dissolution of carbides into austenite is mainly controlled by the partitioning of chromium and manganese between carbides and austenite. The compositional gradients in the microstructure from the Dictra calculations were confirmed by energy dispersive spectrum (EDS) measurements in transmission electron microscope. No significant changes in mechanical properties and microstructure (carbide fraction) could be observed after more than 15 min soaking. However a significant prior austenite grain size growth and as a consequence a larger martensite grain (block) size is observed for long soaking times. © 2020 Elsevier B.V.